Failure of standard antimicrobial therapy in children aged 3-59 months with mild or asymptomatic HIV infection and severe pneumonia - Jeena Prakash; Thea Donald M; MacLeod William B; Chisaka Noel; Fox Matthew P; Coovadia HM; Qazi Shamim (Bulletin of the World Health Organization, 2006)
OBJECTIVE: To determine whether children aged 3-59 months with mild or non-symptomatic human immunodeficiency virus (HIV) infection and WHO-defined severe pneumonia have a higher failure rate than do HIV-uninfected children when treated with the standard WHO treatment of parenteral penicillin or oral amoxicillin. METHODS: This study was a planned sub-analysis of a randomized trial of 3-59-month-old children presenting with WHO-defined severe pneumonia (the APPIS study). We included two sites with high HIV prevalence in Durban, South Africa and Ndola, Zambia. Primary outcome measures were clinical treatment failure at day 2 and day 14. CLINICALTRIALS.GOV IDENTIFIER: CT00227331http://www.clinicaltrialsgov/show/NCT00227331). FINDINGS: Of the 523 children enrolled, HIV status was known for 464 participants; 106 (23%) of these were infected with HIV. By day 2, 57 (12.3%) children had failed treatment and 110 (23.7%) failed by day 14. Twenty (18.9%) HIV-infected children failed by day 2 compared with 37 (10.3%) uninfected children (adjusted odds ratio (OR) 2.07; 95% confidence interval (CI): 1.07-4.00). Thirty-four (32.1%) HIV-infected children failed treatment by day 14 compared with 76 (21.2%) uninfected children (adjusted OR 1.88; 95% CI: 1.11-3.17). Analysis stratified by age showed that the greatest differential in treatment failure at day 2 and day 14 occurred in the children aged 3-5 months. CONCLUSIONS: HIV-infected children with severe pneumonia fail WHO-standard treatment with parenteral penicillin or amoxicillin at day 2 and day 14 more often than do HIV-uninfected children, especially young infants. Standard case management of acute respiratory infection (ARI) using WHO treatment guidelines is inadequate in areas of high HIV prevalence and reappraisal of empiric antimicrobial therapy is urgently needed for severe pneumonia associated with HIV-1.